Self-Directed Learning Competences Assessment of Students after Covid-19 Pandemic - Capozza, Viviana (Community Notebook. People, Education and Welfare in the Society 5.0, 2023)
The use of digital technologies can help learners to undertake self-directed learning paths, as it allows students to study school subjects according to their interests. Given the forced use of these tools due to the Covid-19 pandemic, this study aims to understand which competences were developed by high-school (14-19 years old) students in Rome during this period. For this purpose, for the research project of the Sapienza University of Rome on “The Social Impact Assessment of DaD after Covid-19” (a project still in progress) it was constructed a rubric for the self- assessment of self-directed learning competences that has been proposed within focus groups. The rubric therefore has been used as a stimulus to help students reflect on the way their formal and informal learning experiences have changed because of the pandemic.